2013
DOI: 10.2174/1574888x113086660067
|View full text |Cite
|
Sign up to set email alerts
|

Human Amniotic Fluid Stem Cells Suppress PBMC Proliferation through IDO and IL-10-Dependent Pathways

Abstract: Human amniotic fluid stem cells (hAFSCs) can be readily isolated from human amniotic fluid and display multi-differentiation potential and immunomodulatory properties. The mechanism of hAFSCs immunoregulation has not been defined. Here, we explore the immunomodulatory effects of hAFSCs derived from human amniotic fluid and evaluate the role of IL-10 and the tryptophan-catabolizing enzyme indoleamine 2,3-dioxygenase (IDO) in mediating the immunosuppressive actions of hAFSCs. Flow cytometry showed that hAFSCs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…IDO is one of the key immunoregulators secreted by MSCs, tumors and during pregnancy. IDO is expressed by a wide range of MSCs, like decidual MSCs [167] , amnionic fluid MSC [168] , multipotent adult progenitor cells (MAPCs) [169] , umbilical cord MSCs [170] , AT-MSCs [171] etc. IDO expression is species specific.…”
Section: Indoleamine-23-dioxygenasementioning
confidence: 99%
See 2 more Smart Citations
“…IDO is one of the key immunoregulators secreted by MSCs, tumors and during pregnancy. IDO is expressed by a wide range of MSCs, like decidual MSCs [167] , amnionic fluid MSC [168] , multipotent adult progenitor cells (MAPCs) [169] , umbilical cord MSCs [170] , AT-MSCs [171] etc. IDO expression is species specific.…”
Section: Indoleamine-23-dioxygenasementioning
confidence: 99%
“…Damage associated molecular patterns (DAMPs) are also involved in the IDO expression regulated by MSCs [178] . IDO is expressed after stimuli generated by the crosstalk of MSCs and cells co-cultured with them [168,179] . The cross-talk of MSCs and PBMCs causes increased IL-10 and IDO expression from MSCs that seems to be the mechanism responsible for the immunosuppressive action of the human amnionic fluid stem cells [168] .…”
Section: Indoleamine-23-dioxygenasementioning
confidence: 99%
See 1 more Smart Citation
“…Amniotic fluid‐derived stem cells genetically originate from the fetus itself, thereby allowing for autologous therapeutic applications to be performed without concern for immunologic rejection of donor cells upon delivery, either prenatally or in the early postnatal period . Studies have shown that second‐trimester amniotic fluid stem cells can proliferate rapidly in culture compared to postnatal somatic cells under Good Manufacturing Practice conditions .…”
Section: Rationale For Amniotic Fluid‐derived Stem Cellsmentioning
confidence: 99%
“…Although the mechanistic role of amniotic fluid‐derived MSCs in vivo remains poorly described, MSCs from amniotic fluid have been shown to inhibit T‐cell proliferation, to decrease memory T cells, to increase T regulator lymphocytes, and to polarize the Th2 subtype in association with increased IL‐10 and IL‐4 levels in coculture studies when compared to MSCs derived from bone marrow and placenta . It has been hypothesized that amniotic fluid‐derived MSCs may play a critically important paracrine role in the immune response at the maternal‐fetal interface through expression of the CD59 and HLA‐G, among others .…”
Section: Rationale For Amniotic Fluid‐derived Stem Cellsmentioning
confidence: 99%